Answer: ( -9, 1, 4 )
==================================
Explanation
This system is in row echelon form. We can use back-substitution to start with the value of z to use it to find the value of y, then use y & z values to find the value of x.
------------
Plug z = 4 into the equation with y & z in it. Solve for y
-3y + 2z = 5
-3y + 2*4 = 5
-3y + 8 = 5
-3y + 8 - 8 = 5 - 8
-3y = -3
-3y/(-3) = -3/(-3)
y = 1
-----------
Now plug y = 1 and z = 4 into the first equation. Solve for x.
x + y - 3z = -20
x + 1 - 3*4 = -20
x + 1 - 12 = -20
x - 11 = -20
x - 11+11 = -20+11
x = -9
----------
We get x = -9, y = 1, z = 4.
Therefore, the solution is (x,y,z) = (-9, 1, 4)